Effects of ambroxol hydrochloride on concentrations of paclitaxel and carboplatin in lung cancer patients at different administration times - Li, J.; Yi, W.; Jiang, P.; Sun, R.; Li, T. (Cellular and Molecular Biology, 2016)
Our previous preliminary study revealed a synergistic effect of ambroxol hydrochloride with chemotherapeutic agents such as paclitaxel and carboplatin in lung cancer. However, the optimal conditions such as administration time and drug concentration of ambroxol hydrochloride to achieve the maximum synergistic effect remained unclear. Therefore, concentration changes of the chemotherapy drugs paclitaxel and carboplatin in the sputum were observed after ambroxol hydrochloride administration at different times in order to determine the most effective time frame of ambroxol hydrochloride administration. In this study, 470 cases of non-small cell lung cancer (NSCLC) were divided into different groups with ambroxol hydrochloride administered at different time points prior to chemotherapy, while another 171 cases received no ambroxol hydrochloride prior to chemotherapy. The results showed the concentrations of paclitaxel and carboplatin in sputum of patients treated with ambroxol hydrochloride were significantly higher than those of the control group, suggesting that ambroxol hydrochloride significantly increased the local concentrations of chemotherapeutic agents in lung tissues of NSCLC. Furthermore, the intravenous administration of ambroxol hydrochloride more than 48 hours before chemotherapy showed an optimized schedule and much greater efficacy in increasing drug concentrations than that of the control group. No statistical differences were found in the rates of grade 2 or above myelosuppression between the ambroxol intervention and control groups. Taken together, these results demonstrate that ambroxol hydrochloride administered intravenously more than 48 hours prior to chemotherapy optimally increased the concentrations of paclitaxel and carboplatin in lung tissue without significantly increasing hematologic toxicity.